DETERMINATION OF PROTEIN TRANSPORTERS FOR THE ABSORPTION OF ZN-PEPTIDES FROM HOLOTHURIA SCABRA THROUGH NETWORK PHARMACOLOGY WITH MOLECULAR SIMULATION APPROACH - SYAHPUTRA, GITA; LOUISA, MELVA; PUTRA, MASTERIA YUNOVILSA; WIJAYANTI, RINA; GUSTINI, NUNIK; ROSYIDAH, A’LIYATUR (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to identify key genes and proteins involved in zinc homeostasis and to evaluate the potential of sea cucumber (Holothuria scabra) peptides as zinc-binding agents targeting the zinc transporter protein ZIP2, which plays a central role in zinc deficiency. Methods: Bioinformatics analyses were conducted to identify genes associated with zinc deficiency and related pathways. Protein–protein interaction (PPI) networks were used to determine key target genes involved in zinc homeostasis. Molecular docking simulations assessed the binding affinity of six H. scabra peptides to the ZIP2 protein compared with ZnSO₄ and Zn-carnosine as controls. Molecular dynamics (MD) simulations, including RMSD and RMSF analyses, were performed to evaluate the stability and interaction dynamics of the most promising peptide–protein complex. Results: A total of 90 target genes associated with zinc deficiency were identified, involving multiple biological processes and pathways. Ten key protein-coding genes were found to play significant roles in zinc homeostasis, including nine zinc transporter genes (SLC39A2, SLC30A3, SLC39A4, SLC30A2, SLC30A4, SLC39A13, SLC29A8, TEX11, and C904f84) and one zinc-sensing receptor gene (GPR39). PPI network analysis revealed SLC39A2 (ZIP2) as the central gene in zinc homeostasis. Among the six tested peptides, the PY peptide exhibited the most favorable binding affinity to ZIP2 (-6.1 kcal/mol), surpassing both control compounds. MD simulations indicated stable interaction of the PY peptide at the active site of ZIP2 throughout the observation period. Conclusion: The study highlights SLC39A2 (ZIP2) as a pivotal protein in zinc homeostasis and identifies the PY peptide from H. scabra as a promising zinc-binding agent. These in silico findings provide a foundation for future in vitro and in vivo investigations into potential peptide-based interventions for zinc deficiency.